2015
DOI: 10.1073/pnas.1421392112
|View full text |Cite
|
Sign up to set email alerts
|

An ancestral bacterial division system is widespread in eukaryotic mitochondria

Abstract: Bacterial division initiates at the site of a contractile Z-ring composed of polymerized FtsZ. The location of the Z-ring in the cell is controlled by a system of three mutually antagonistic proteins, MinC, MinD, and MinE. Plastid division is also known to be dependent on homologs of these proteins, derived from the ancestral cyanobacterial endosymbiont that gave rise to plastids. In contrast, the mitochondria of model systems such as Saccharomyces cerevisiae, mammals, and Arabidopsis thaliana seem to have rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 89 publications
(62 reference statements)
0
59
0
Order By: Relevance
“…The most widespread eukaryotic organelle with bacterial ancestry is the mitochondrion. An extensive set of organellar functions are clearly of direct ancestry from α-proteobacteria, including organelle maintenance and replication (Leger et al, 2015), much of aerobic energy metabolism (Müller et al, 2012, as well as others) and even some recent surprises about organelle morphology, such as the mitochondrial contact site (MICOS) complex that is responsible for cristae formation (Muñoz-Gómez et al, 2016). The α-proteobacterial contribution can also be seen in other processes, such as in Fe-S cluster formation (Barberà et al, 2010), β-oxidation of fatty acids (Bolte et al, 2015), the glycine cleavage system (Nývltová et al, 2015) and hemebiosynthesis (Cenci et al, 2016).…”
Section: Towards Revealing the Prokaryotic Origins Of Eukaryotic Cellmentioning
confidence: 99%
“…The most widespread eukaryotic organelle with bacterial ancestry is the mitochondrion. An extensive set of organellar functions are clearly of direct ancestry from α-proteobacteria, including organelle maintenance and replication (Leger et al, 2015), much of aerobic energy metabolism (Müller et al, 2012, as well as others) and even some recent surprises about organelle morphology, such as the mitochondrial contact site (MICOS) complex that is responsible for cristae formation (Muñoz-Gómez et al, 2016). The α-proteobacterial contribution can also be seen in other processes, such as in Fe-S cluster formation (Barberà et al, 2010), β-oxidation of fatty acids (Bolte et al, 2015), the glycine cleavage system (Nývltová et al, 2015) and hemebiosynthesis (Cenci et al, 2016).…”
Section: Towards Revealing the Prokaryotic Origins Of Eukaryotic Cellmentioning
confidence: 99%
“…The bacterial divisome complex, which is built around the polymers of a tubulin ortholog, the GTPase FtsZ, has been entirely replaced in the mitochondria of many eukaryote lineages by proteins of the dynamin superfamily [17]; yet, eukaryotes that have preserved the original FtsZ-based machinery can still be found in all eukaryotic supergroups [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Miyagishima et al (4) concluded that FtsZ2 in green plants and algae and FtsZA in red algae descended from the original single FtsZ from the cyanobacterium and that FtsZ1 and FtsZB arose by separate gene duplications. There is a similar duplication of FtsZ in the mitochondria that have kept FtsZ, one with and one without the C-terminal peptide (4,19). As in Arabidopsis, the FtsZ with the C-terminal peptide may interact with a membrane protein to tether the Z ring, whereas the one without may play a regulatory role.…”
mentioning
confidence: 98%